A Comparative Study of Social-Ecological Characteristics of Land-based and Island-based Small-Scale Fisheries in Southeast Sulawesi Province - Ariston, Muhamad; Adrianto, Luky; Bengen, Dietriech G; Susanto, Handoko Adi; Zulfikar, Andi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Small-scale fisheries exhibit unique, diverse, and varied characteristics in each region. These distinctive traits render small-scale fisheries challenging to regulate centrally. This research aims to compare the characteristics of land-based and island-based small-scale fisheries in Southeast Sulawesi Province. Data were collected through structured interviews involving 445 respondents from two distinct areas: North Konawe, representing land-based fisheries, and Konawe Islands, representing island-based fisheries. Both qualitative (questionnaire data) and quantitative analyses were conducted using R software. Proportion data were tested using the R ggstatsplot package, while word cloud analysis utilized the R wordcloud package. The analysis of fishing ground distribution hotspots was performed using QGIS software version 3.30. The research findings demonstrate differences across various aspects, including education levels, boat sizes, fishing frequency, monthly income, and types of captured fish. Furthermore, the study highlights that island-based small-scale fisheries hold a higher income potential compared to their landbased counterparts. These differing characteristics serve as essential considerations in developing policies that support sustainable management of small-scale fisheries based on the needs of local communities.